Pengembangan Video Interaktif Macromedia Flash pada KD Hidangan dari Telur untuk Siswa SMK Tata Boga - Adinda Putri Cahyani; Sri Handajani; Niken Purwidiani; Asrul Bahar (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research are: 1) to know the results of the development of interactive video learning media based on macromedia flash; 2) to know the feasibility of material and media on interactive learning media based on macromedia flash; and 3) to know the students' response to interactive learning media based on macromedia flash on basic competence analyzing dishes from eggs. The development model used the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation. However, this study only reached the development stage because it only aims to produce interactive video products. The data collection technique used a questionnaire with the subject of 2 material expert validators, 2 media expert validators, and grade XI Tata Boga students at SMKN 2 Mojokerto. The data analysis technique used is descriptive analysis technique. The research showed: 1) the media has been developed with the ADDIE method (up to stage 3) and can be accessed by students via gdrive; 2) the feasibility of material and media shows very feasible results (3.53 and 3.56); and 3) student responses show very good (3.38). It can be concluded that the interactive video learning media based on macromedia flash on basic competencies dishes from eggs for grade XI students of vocational school of culinary is highly suitabel to use in learning.